HUBUNGAN SELF-COFIDENCE DENGAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP - Siti Muniroh; Tina Rosyana; Heris Hendriana (IKIP Siliwangi, 2018)
This study examines the relationship between self-confidence with students' mathematical communication skills. This research uses expost pacto method with correlation analysis technique. The population in this study is all students of class IX in one of the SMP Negri in Cimahi city (IX.A - IX.N) with the number of 504 students / The academic year 2017/2018. As for the sample in this study is the students of SMP class IX N with the number of 36 students / i. In this study using cluster random sampling technique that is random sampling. In the data collection is by using the questionnaire instrument (self-confidence questionnaire) and test of mathematical communication skills. Further data is analyzed quantitatively by using Pearson correlation formula in SPSS application. The results showed that there was a positive relationship between self-confidence with students' mathematical communication ability, with correlation coefficient value of 0.865 and Sig. (2-tailed) 0.000.